Associations of regular glucosamine use with all-cause and cause-specific mortality: a large prospective cohort study. Issue 6 (6th April 2020) - Li, Zhi-Hao; Gao, Xiang; Chung, Vincent CH; Zhong, Wen-Fang; Fu, Qi; Lv, Yue-Bin; Wang, Zheng-He; Shen, Dong; Zhang, Xi-Ru; Zhang, Pei-Dong; Li, Fu-Rong; Huang, Qing-Mei; et al.
Abstract : Objectives: To evaluate the associations of regular glucosamine use with all-cause and cause-specific mortality in a large prospective cohort. Methods: This population-based prospective cohort study included 495 077 women and men (mean (SD) age, 56.6 (8.1) years) from the UK Biobank study. Participants were recruited from 2006 to 2010 and were followed up through 2018. We evaluated all-cause mortality and mortality due to cardiovascular disease (CVD), cancer, respiratory and digestive disease. HRs and 95% CIs for all-cause and cause-specific mortality were calculated using Cox proportional hazards models with adjustment for potential confounding variables. Results: At baseline, 19.1% of the participants reported regular use of glucosamine supplements. During a median follow-up of 8.9 years (IQR 8.3–9.7 years), 19 882 all-cause deaths were recorded, including 3802 CVD deaths, 8090 cancer deaths, 3380 respiratory disease deaths and 1061 digestive disease deaths. In multivariable adjusted analyses, the HRs associated with glucosamine use were 0.85 (95% CI 0.82 to 0.89) for all-cause mortality, 0.82 (95% CI 0.74 to 0.90) for CVD mortality, 0.94 (95% CI 0.88 to 0.99) for cancer mortality, 0.73 (95% CI 0.66 to 0.81) for respiratory mortality and 0.74 (95% CI 0.62 to 0.90) for digestive mortality. The inverse associations of glucosamine use with all-cause mortality seemed to be somewhat stronger among current than non-current smokers (p for interaction=0.00080). Conclusions: Regular glucosamine supplementation was associated with lower mortality due to all causes, cancer, CVD, respiratory and digestive diseases.